Clinicopathological characteristics and prognosis of early-stage HER2 low-expression breast cancer: A single-center retrospective study - Liu, Chang-Gen; Li, Yi-Fan; Ma, Tian-Yi; Lv, Meng; Lv, Zhi-Dong; Wang, Yuan-Yuan; Liu, Xiang-Ping; Mao, Yan; Wang, Hai-Bo (Frontiers in Oncology, 2023)
Background Owing to the emergence of drugs targeting human epidermal growth factor receptor 2 (HER2), remarkable prognostic enhancement has been seen for patients with HER2-positive breast carcinoma. However, anti-HER2 medicines are applicable merely to individuals with HER2-positive tumors, and the benefit for those with low HER2 expression is unclear. The DESTINY-Breast04 phase III and RC48 clinical trial results showed the benefit of antibody-drug couples for low HER2-expressing individuals with breast carcinoma, challenging the traditional dichotomy between HER2-negative and -positive tumors. Hence, the purposes of the present work are to explore the clinicopathological traits and prognostic differences in the HER2-low expression Chinese population with early-stage breast carcinoma. Methods Data from the database of the Breast Center of the Affiliated Hospital of Qingdao University were collected from January 2008 to December 2017. We screened a total of 4,598 patients, of which 2,837 had HER2-0 tumors and 1,761 had HER2-low tumors. Additionally, clinicopathological characteristics, survival, and prognostic information were obtained. Difference comparisons were made between HER2-0 and HER2-low groups regarding the clinical traits and outcomes. Results We enrolled 4598 patients, with the HR-positive subjects suffering from HER2-low breast carcinoma higher in proportion than the HR-negative patients. In contrast to HER2-0 tumors, the HER2-low tumors were linked to an older median age at diagnosis, T1 tumors, N1 stage, a higher Ki-67 index, as well as inferior histological grade. Insignificant inter-group difference was noted regarding overall survival (OS), although the HER2–0 group exhibited better disease-free survival (DFS) than the HER2-low group for the entire (P = 0.003), lymph node-negative (P = 0.009) and HR-positive (P = 0.007) populations. According to the multivariate regression finding, low HER2 expression was an inferior DFS prognostic factor in the HER2-negative population with early-stage breast cancer (HR,1.33;95% CI, 1.06-1.66; P = 0.013). Conclusion The clinical traits of the HER2-low carcinomas differed from those of HER2–0 tumors. Despite the insignificant inter-group difference in OS, the differences in DFS were found for the overall, lymph node-negative and HR-positive subjects, suggesting the possibility of HER2-low as an inferior prognostic factor for disease progression in early-stage breast cancer.